The open-mind diagram as a cooperative learning strategy to develop the english as foreign language basic writing skills amongst ninth-grade students, group “a” at profesor. Julio Ordoñez Espinoza high school, 2014 – 2015 academic period - Cajamarca Llivigañay, Mayra Ivonn (2016)
This action research entitled: the Open-Mind diagram as a cooperative learning strategy to develop the English as foreign language basic writing skills amongst ninth-grade students, group ―A‖ at Profesor. Julio Ordoñez Espinoza high school, 2014 – 2015 academic period., as a main objective it was proposed to improve the English Foreign language basic writing skills through the Open-Mind diagram as a cooperative learning strategy. For its development, it was used the: Scientific, descriptive, analytic-synthetic and statistic methods; the instruments used were the pre and post test, pre and post questionnaire and the observation sheet in order to evaluate the students’ knowledge in basic writing skills, the behavior and attitudes toward the Open-Mind diagram before, during and after the intervention. It was concluded that the eighteen students from ninth-grade improved considerably their writing skills based on cooperative leaning, increasing a score from 3,32 to 8,17 out of 10.